2014
DOI: 10.5039/agraria.v9i2a3178
|View full text |Cite
|
Sign up to set email alerts
|

Modeling preslaughter mortality of broiler chickens using double generalized linear models

Abstract: The aim of this study was to estimate parameters and design models for mortality prediction of broiler chickens in different preslaughter conditions, using the double generalized linear models. Preslaughter data from 13,937 broiler flocks were recorded daily during 2006, in a commercial slaughterhouse in Brazil. Several factors which influenced mortality rate were analysed, such as daily mean drybulb temperature and relative humidity, lairage time, daily periods, density of broilers per crate and season of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
3

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 30 publications
0
1
0
3
Order By: Relevance
“…A study on 13937 transportation operations in Brazil in 2006 indicated that the average mortality rate for transportation distances ranging from 24 km to 242 km was 0.33%, with the highest mortality rate recorded during summer (0.42%) (Vieira et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…A study on 13937 transportation operations in Brazil in 2006 indicated that the average mortality rate for transportation distances ranging from 24 km to 242 km was 0.33%, with the highest mortality rate recorded during summer (0.42%) (Vieira et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…O quesito transporte ficou falho no manual brasileiro que apenas detalha a questão da presença da guia, enquanto o Manual da Fawc fez uma descrição mais elaborada em seu texto. Apesar do Manual da Fawc apresentar texto mais bem elaborado que o brasileiro, os autores (Silva, et al, 2011 2016, Rui et al, 2011, Vieira et al, 2014e Vieira et al, 2015 colocam outros quesitos importantes no transporte que não foram abordados no texto legal de nenhum dos manuais, como o estresse térmico das aves que é associado ao aumento do percurso de transporte e tem como consequência o maior índice de mortalidade, as estações do ano, as elevadas temperaturas e umidades relativas que contribuem efetivamente para o estresse térmico durante todas as operações pré-abate.…”
Section: Resultsunclassified
“…Informações adequadas sobre os seguintes itens foram consideradas na comparação: jejum (Rui et al, 2011;Muller, et al, 2012), captura (Vecerek et al, 2016), carregamento (Aral et al, 2014), transporte (Vieira, et al, 2014;Weeks, 2014) e tempo de espera no abatedouro (Oliveira, 2011). Foram construídas tabelas e a média das pontuações foi calculada tanto para o tipo específico de demanda quanto para o Brasil e Europa, a fim de verificar e quantificar o quanto eles se afastam ou concordam com o código internacional na parte de transporte animal selecionados.…”
Section: Methodsunclassified
See 1 more Smart Citation